Impact of low-density lipoprotein cholesterol and lipoprotein(a) on mid-term clinical outcomes following coronary artery bypass grafting: A secondary analysis of the DACAB trial - Yu, Qixiang; Xue, Qing; Liu, Hao; Hu, Junlong; Wang, Rui; Song, Yuanyuan; Zhou, Yanzai; Zhang, Wei; Zhu, Yunpeng; Zhao, Qiang (Frontiers in Cardiovascular Medicine, 2023)
Purpose The objective was to evaluate the influence of low-density lipoprotein cholesterol (LDL-C) and lipoprotein(a) [Lp(a)] on clinical outcomes in patients undergoing coronary artery bypass grafting (CABG). Methods This is a secondary analysis of a 5-year follow-up of the DACAB trial (NCT02201771), in which 500 patients who underwent primary isolated CABG were randomized to three-antiplatelet therapy for 1 year after surgery. Of them, 459 patients were recruited in this secondary analysis. Baseline LDL-C and Lp(a) levels were collected, and repeated measurement of LDL-C levels during the follow-up were recorded. Cut-off values for LDL-C were set at 1.8 and 2.6 mmol/L; thus, the patients were stratified into LDL-C <1.8, 1.8–<2.6, and ≥2.6 mmol/L subgroups. Cut-off value for Lp(a) was 30 mg/dL; thus, the patients were divided into Lp(a) <30 and ≥30 mg/dL subgroups. The primary outcome was 4-point major adverse cardiovascular events (MACE-4), a composite of all-cause death, myocardial infarction, stroke, and repeated revascularization. Median follow-up time was 5.2 (interquartile range, 4.2–6.1) years. Results During the follow-up, 129 (28.1%) patients achieved the attainment of LDL-C <1.8 mmol/L, 186 (40.5%) achieved LDL-C 1.8–<2.6 mmol/L, and 144 (31.4%) remained LDL-C ≥2.6 mmol/L. Compared with the postoperative LDL-C <1.8 mmol/L group, the risk of MACE-4 was significantly higher in the LDL-C 1.8–<2.6 mmol/L group [adjusted hazard ratio (aHR) = 1.92, 95% CI, 1.12–3.29; P = 0.019] and LDL-C ≥2.6 mmol/L group (aHR = 3.90, 95% CI, 2.29–6.64; P < 0.001). Baseline Lp(a) ≥30 mg/dL was identified in 131 (28.5%) patients and was associated with an increased risk of MACE-4 (aHR = 1.52, 95% CI, 1.06–2.18; P = 0.022). Conclusions For CABG patients, exposure to increased levels of postoperative LDL-C or baseline Lp(a) was associated with worse mid-term clinical outcomes. Our findings suggested the necessity of achieving LDL-C target and potential benefit of adding Lp(a) targeted lipid-lowering therapy in CABG population.